Cadets weight-lifters power indices study during preparatory period of sports training - Grankin, N. A. (The Russian Journal of Physical Education and Sport, 2016)
The system of power training improvement in power kinds of sport is still very urgent at all stages of sports training. In spite of a lot of research works, connected with power training of sportsmen, it needs correction, different new innovative technologies of sports training creation. The problem of effectiveness increase of power training among cadets-weight-lifters by means endurance upbringing and respiratory system development is still urgent. Research methods. Power indices testing using hands dynamometry, back strength, weight press from lying support;mathematical treatment of results. Materials. The results of power indices testing among cadets-weight-lifters before and after the pedagogical experiment are presented. A positive dynamics of hands dynamometry indices,back strength and weight press is pointed out. Results. During the pedagogical testing the change of the studied indices among cadets-weight-lifters was determined. A comparative analysis of power indices was held. An authentic increase of hands dynamometry, back strength and weight press indices among cadets from the experimental group is determined. Conclusion. Thus, after the pedagogical experiment the following indices of power training among cadets-weight-lifters from the control group and the experimental group were revealed: right hand dynamometry in the control group - 38,84±0,49 kg, in the experimental group - 43,72±0,47 kg; left hand dynamometry: in the control group - 39,96±0,75 kg, in the experimental group - 43,53±0,63kg; back strength in the control group - 109,87±1,01 kg, in the experimental group - 123,67±1,71 kg; weight press from lying support in the control group - 71,82±1,04 kg, in the experimental group - 65,60±0,71 kg.